Ehrlichia chaffeensis Infection in the Reservoir Host (White-Tailed Deer) and in an Incidental Host (Dog) Is Impacted by Its Prior Growth in Macrophage and Tick Cell Environments - Nair, Arathy D. S.; Cheng, Chuanmin; Jaworski, Deborah C.; Willard, Lloyd H.; Sanderson, Michael W.; Ganta, Roman R. (My University, 2014)
Ehrlichia chaffeensis, transmitted from Amblyomma americanum ticks, causes human monocytic ehrlichiosis. It also infects white-tailed deer, dogs and several other vertebrates. Deer are its reservoir hosts, while humans and dogs are incidental hosts. E. chaffeensis protein expression is influenced by its growth in macrophages and tick cells. We report here infection progression in deer or dogs infected intravenously with macrophage- or tick cell-grown E. chaffeensis or by tick transmission in deer. Deer and dogs developed mild fever and persistent rickettsemia; the infection was detected more frequently in the blood of infected animals with macrophage inoculum compared to tick cell inoculum or tick transmission. Tick cell inoculum and tick transmission caused a drop in tick infection acquisition rates compared to infection rates in ticks fed on deer receiving macrophage inoculum. Independent of deer or dogs, IgG antibody response was higher in animals receiving macrophage inoculum against macrophage-derived Ehrlichia antigens, while it was significantly lower in the same animals against tick cell-derived Ehrlichia antigens. Deer infected with tick cell inoculum and tick transmission caused a higher antibody response to tick cell cultured bacterial antigens compared to the antibody response for macrophage cultured antigens for the same animals. The data demonstrate that the host cell-specific E. chaffeensis protein expression influences rickettsemia in a host and its acquisition by ticks. The data also reveal that tick cell-derived inoculum is similar to tick transmission with reduced rickettsemia, IgG response and tick acquisition of E. chaffeensis.
Citation: Nair, A. D. S., Cheng, C., Jaworski, D. C., Willard, L. H., Sanderson, M. W., & Ganta, R. R. (2014). Ehrlichia chaffeensis Infection in the Reservoir Host (White-Tailed Deer) and in an Incidental Host (Dog) Is Impacted by Its Prior Growth in Macrophage and Tick Cell Environments. PLOS ONE, 9(10), e109056. https://doi.org/10.1371/journal.pone.0109056
Keywords: Deer; Dogs; Macrophages; Pathogens; Blood; Antibody Response